العنوان : مبدأ الفصل بين السلطات في ظل التعديل الدستوري في 2016 من خلال علاقة السلطة التنفيذية بالسلطة التشريعية - الطاوس, بن حمو (Université de M'sila, 2020)
الملخص: إن مبدأ الفصل بين السلطات له مكانة مهمة عند الدستوريين و ذلك لاعتباره كمعيار لتصنيف الأنظمة السياسية في الدول، فهو المبدأ الذي يهدف إلى عدم تركيز السلطات في يد هيئة واحدة ، إلا ان النظام السياسي الجزائري ذو الطبيعة الخاصة يقوم على فكرة تقسيم السلطات و الوظائف في ظل وحدة القيادة و الواضح من خلال هيمنة و تدخل السلطة التنفيذية في مجال اختصاص السلطة التشريعية و كذا وسائل تأثير السلطة التنفيذية على السلطة التشريعية، و هي فكرة تتنافى و مبدأ الفصل بين السلطات الذي يقتضي استقلالية كل سلطة عن الأخرى مع وجود تعاون فيما بينها، و إن كان المؤسس الدستوري الجزائري لم يقر صراحة هذا المبدأ إلا في التعديل الدستوري الأخير في 2016. ABSTRACT : The principle of separation of powers has an important standing for the Constitutionals, as it is considered as a criterion for classifying the political systems of States, a principle that aims to the lack of concentration of powers in the hands of a single body, but the Algerian political system of a special nature is based on the idea of dividing powers and functions under single leadership which is obvious through the dominance and interference of the executive in the jurisdiction of the legislature, as well as the means of influencing the executive on the legislative power, which is an idea contrary to the principle of separation of powers, that requires the independence of each power from the other with cooperation between them, although the Algerian constitutional founder doesn’t explicitly recognize this principle only in the constitutional amendment of 2016.
Keywords: الكلمات المفتاحية :فصل السلطات ،تركيز السلطة ،النظام السياسي ، السلطة التنفيذية ، المؤسس الدستوري الجزائري. ; KEY WORDS: Separation of powers, concentration of powers, political systems, executive power, Algerian constitutional founder